Financial Performance Assessment through Statement Analysis: A Qualitative Study: Penilaian Kinerja Keuangan melalui Analisis Laporan: Studi Kualitatif - Adelefano , Mohammad Rizky; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2023)
This qualitative study aims to assess the financial performance of a regional water company using descriptive analysis. Conducted at a specific location in Pasuruan Regency, East Java, the research gathered insights from experts in the Finance Division and General Affairs, Public Relations, and HR. Inductive data analysis revealed increasing liquidity ratios, decreasing solvency ratios, and rising profitability ratios over the years. These findings carry implications for the financial health and sustainability of similar entities, offering valuable insights for decision-makers in the water utility sector. Highlights: Key Insight: Qualitative approach for financial assessment. Notable Trends: Liquidity, solvency, and profitability ratios. Sector Implications: Decision support for water utilities. Keywords: Financial Performance, Statement Analysis, Water Utility, Qualitative Research, Sustainability.